2017
DOI: 10.1002/polb.24377
|View full text |Cite
|
Sign up to set email alerts
|

Cononsolvency of poly(N‐isopropylacrylamide) in methanol aqueous solution—insight by dielectric spectroscopy

Abstract: Both water and methanol are good solvents for poly(N‐isopropylacrylamide) (PNIPAM), while PNIPAM does not dissolve in their mixed solvents, this phenomenon is called cononsolvency. Cononsolvency is closely related to many phenomena in life but so far, its mechanism is still controversial. In this work, the dielectric behavior of PNIPAM methanol aqueous solution was studied in the frequency of 40Hz–40GHz. From lower frequency to higher frequency, four relaxations were found. They are, respectively, from global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
2
17
0
1
Order By: Relevance
“…As we have shown, many of these changes arise essentially from an intrinsic property of the pNIPAm chain, namely the temperature-induced change of the interchain interactions and the mixing scheme of pNIPAm in aqueous environment. We anticipate that this work has a potential impact on subsequent investigation into effects of coexisting alcohols [15,16,31] and ions on the phase transition of pNIPAm and all kinds of other thermoresponsive polymers in aqueous media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have shown, many of these changes arise essentially from an intrinsic property of the pNIPAm chain, namely the temperature-induced change of the interchain interactions and the mixing scheme of pNIPAm in aqueous environment. We anticipate that this work has a potential impact on subsequent investigation into effects of coexisting alcohols [15,16,31] and ions on the phase transition of pNIPAm and all kinds of other thermoresponsive polymers in aqueous media.…”
Section: Discussionmentioning
confidence: 99%
“…Hydration effects and dynamics of pNIPAm have been extensively studied by spectroscopic techniques [22][23][24][25][26][27][28][29][30][31][32]. Dehydration behavior during the phase transition was investigated by dielectric relaxation spectroscopy (DRS), although the number of experimental data points are limited [24,28].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is called cononsolvency ( 26 , 27 ). Precise mechanisms leading to a collapse and a slight preferential partitioning of one solvent species inside the gel are still under controversial debate ( 28 33 ). These details, however, will be mainly relevant on a local length scale and thus on a very short time scale, whereas the process of gel collapse concerns much larger length and longer time scales and hence can be considered as generic, which is also supported by our results discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…( 12 ), Lu and Ballauf ( 15 ), Bischofberger et al . ( 32 ), Yang and Zhao ( 33 ), Maccarrone et al . ( 34 ), Stieger et al .…”
Section: Introductionunclassified
“…Recently, we have successfully prepared macroscopic cellulose gel beads by precipitating cellulose/LiCl/DMAc solutions into a nonsolvent (ethanol or water). These beads have been used as models to investigate the swelling behavior of the wet, delignified cellulosic fibers of wood . These nanometer smooth dried cellulose beads have also been used as probes to conduct contact adhesion measurements between cellulose and other materials. , NMR and SAXS measurements of the beads in the wet state indicate that the internal structure of macroscopic cellulose gel beads can be considered as a microgel system whereby the cellulose forms a homogeneous, noncrystalline, and molecularly dispersed polymer network. , Many studies have been conducted to elucidate the equilibrium structures of a variety of microgel systems with different chemistries in swollen or collapsed states. Kinetic studies of the structural response of swelling and deswelling microgels have been reported. However, there are few studies investigating the kinetics of microstructure changes within microgel beads during drying .…”
mentioning
confidence: 99%